TINJAUAN LITERASI ATAS PERKEMBANGAN AKUNTANSI SYARIAH DI INDONESIA - Adi Cahyo, Wisnu Handika; Latifah, Eny (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This research aims to analyse the development of Islamic Accounting in Indonesia with a focus on principles, practices, as well as its impact on Islamic financial institutions. The research method includes literature analysis, case study. The results showed that a comprehensive overview of the development of Islamic Accounting in Indonesia, where significant developments in recent decades, especially along with the growth of Islamic financial institutions in the country. A comparison between Islamic Accounting and conventional Accounting reveals differences in principles, practices, and impacts. Islamic Accounting considers Islamic ethical values, sustainable profitability, and social justice in accounting practices. The results of this study provide important insights for practitioners, regulators, and researchers in understanding the dynamics of Islamic Accounting and its implications for Islamic financial institutions in Indonesia.